2014
DOI: 10.3892/ol.2014.1936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 14 frequently used drugs on prostate-specific antigen expression in prostate cancer LNCaP cells

Abstract: Prostate cancer occurs more frequently among older males and such elderly individuals often have chronic underlying disorders for which various drugs are administered for treatment. The levels of prostate-specific antigen (PSA), a widely used prostate cancer marker, are influenced by a number of drugs, such as non-steroidal anti-inflammatory drugs and statins. In the present study, the drugs prescribed to patients on a repeat prescription collected at the pharmacy of the Gifu Pharmaceutical University (Gifu, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…37 In addition to increased testosterone concentrations, decreased BMI, IR, and HbA 1c , 38,39 some other factors can also influence PSA changes: older age, recent ejaculation, certain medications (statin and betamethasone). [40][41][42] We observed no cases of PCa.…”
Section: Discussionmentioning
confidence: 54%
“…37 In addition to increased testosterone concentrations, decreased BMI, IR, and HbA 1c , 38,39 some other factors can also influence PSA changes: older age, recent ejaculation, certain medications (statin and betamethasone). [40][41][42] We observed no cases of PCa.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, a recent study suggested that obese men have lower PSA levels, as compared to normal weight men, possibly due to hormonal changes especially by an elevated E2/testosterone ratio and hemodilution [ 44 ]. Furthermore, PSA levels are influenced by a number of drugs, such as non-steroidal anti-inflammatory drugs, statins and thiazide diuretics [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSA is a widely used biomarker for PCa and has been recommended as a tool for the screening of PCa and as a follow-up marker for PCa therapy. A study investigating the effects of 14 commonly prescribed drugs on the expression of PSA mRNA in PCa cells (LNCaP cells) showed that except for a positive effect of betamethasone, all other drugs including metformin and insulin did not significantly affect PSA expression [ 66 ]. A later study using LNCaP cells also did not find an effect of metformin on PSA [ 67 ].…”
Section: Prostate-related Healthmentioning
confidence: 99%